Triangular resection versus folding repair for simple posterior mitral leaflet lesions: case-control study - Nakamura, Ken (Cardiovasc Diagn Ther, 2020)
BACKGROUND: A triangular resection (TR)/suture of the posterior leaflet lesion is the most common technique in mitral valve repair procedures. However, posterior leaflet motion is restricted after surgical resection in echocardiogram analyses. Although several reports have compared the resection/suture technique and the artificial chorda technique, few reports have compared TR with folding repair (FR). We compared the effectiveness and short-term impact of the TR and non-resection-based FR procedures on patients undergoing mitral valve repair. METHODS: Mitral valve repair was conducted on 36 patients with moderate to severe mitral regurgitation (MR) through either TR (n=18) or FR (n=18). Echocardiographic data were collected pre- and post-operatively. Routine echocardiographic follow-ups were performed for each patient. Data were analyzed using t-test, Mann-Whitney U-test, chi-squared analysis, or Fisher’s exact test. P values <0.05 were considered significant. RESULTS: Operative time and length of stay within the intensive care unit and hospital did not significantly differ between the two techniques. Post-operative echocardiographic results showed a significantly larger mitral valve area after FR (P=0.029). The regurgitation regression rate was 94% under mild MR in the FR group (1 case; severe) and 88.8% in the TR group (2 cases; moderate) during the same duration. CONCLUSIONS: Both techniques showed comparable outcomes and durability. However, FR is relatively simple and it is possible to re-initiate FR procedures; thus, it may also provide an opportunity for less-experienced surgeons to conduct valve repair surgeries. The study was registered with the University Hospital Medical Information Network (study ID: UMIN000039041).